2010
DOI: 10.1111/j.1651-2227.2010.02074.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroids for preterm birth: dose‐dependent reduction in birthweight, length and head circumference

Abstract: Multiple courses of ACS are associated with a dose-dependent decline in foetal growth, which may affect later development and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Prenatally repeated dosages of corticosteroids seem to have an association with a smaller birth size in weight, height, and head circumference. (25,26) There is one study that shows that there is no difference in weight, height, and head circumference at the age of two years between the preterm infants who received multiple courses of antenatal steroids and a placebo group. (27) We did not find any difference in infant growth rates in length or growth markers between the infants who either had or had not been exposed to maternal corticosteroid therapy prenatally, but repeated doses were not used.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatally repeated dosages of corticosteroids seem to have an association with a smaller birth size in weight, height, and head circumference. (25,26) There is one study that shows that there is no difference in weight, height, and head circumference at the age of two years between the preterm infants who received multiple courses of antenatal steroids and a placebo group. (27) We did not find any difference in infant growth rates in length or growth markers between the infants who either had or had not been exposed to maternal corticosteroid therapy prenatally, but repeated doses were not used.…”
Section: Discussionmentioning
confidence: 99%
“…Since the trials conducted by Liggins and Howie in 19726), many observational and controlled studies have reported that antenatal administration of glucocorticoids (GCs) to mothers at risk of preterm birth decreases the severity of respiratory distress syndrome and improves the survival of preterm infants6,7,8,9,10). However, repeated courses of antenatal GCs may be associated with reduced fetal brain growth and long-term neurodevelopmental impairment10,11,12,13,14,15,16,17). Several studies of systematic reviews and meta-analyses have shown that postnatal use of GCs to prevent or treat chronic lung disease (CLD) in preterm infants may facilitate extubation and decrease the incidence of bronchopulmonary dysplasia (BPD), but have found that it increases the risk of neurodevelopmental impairment and cerebral palsy (CP), particularly in infants treated with dexamethasone within the first week of life2,3,4,5,18,19,20,21,22,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the programming has its roots since 50 years ago (163) and proven by both animal (152,164) and human studies (119,149), however, the mechanism that events during intrauterine life are carried in the memory of every molecule, gene, cell, tissue and systems` organs of the body still not completely revealed. Many hypotheses have been proposed with their inherited power and weakness.…”
Section: Proposed Mechanism Of Fetal Programming Of Adult Diseasementioning
confidence: 99%
“…In fact, multiple courses of antenatal GCs have been found to be associated with reduction in ponderal measurements including birth weight, height (116)(117)(118)(119)(120) and birth head circumference (117,119,121) and higher infant blood pressure and myocardial wall thickness (122,123) also with maternal infection such as chorioamnionitis and endometritis (116,121,124). Rodríguez-Pinilla also reported that antenatal exposure to single steroid course is able to produce similar effects of multiple courses on birth weight and height but not head circumference (117).…”
Section: Antenatal Synthetic Steroid (Dexamethasone and Betamethsone)mentioning
confidence: 99%